(untitled) (Global Journal of Management and Business Research, 2021)
Contemporary consumers look for those brands which provide them remarkable brand experience. In dynamic telecom industry marketers always try to create and maintain strong customer relationship by establishing effective marketing strategies as it is a significant achievement aspect that enhances the competitiveness level of an organization. The purpose of the research is to investigate the impact of the various feature of brand experience (sensory, affective, and intellectual) on brand satisfaction and brand loyalty. For achieving these objectives, a total of 120 consumers participated in this study. They completed a structured questionnaire, and the information of this study is analyzed using SPSS. Nonprobability sample technique used to gather data from respondents. The study shows that good internal consistency presents here as we use Cronbach’s Alpha to measure this internal consistency in our reliability test. From the findings, it is identified that there are variations in the different aspects of brand experience (sensory, affective, and intellectual) across the brands.